PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM MELALUI MODEL MANAJEMEN MENTORING DI UKM KEROHANIAN IAIN CURUP - Lukman A; Ade Surya; Asri Karolina; Ade Kurniawan (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
This study aimed to find the answers about inculcating Islamic education values through a mentoring model in the student activity unit (SAU) of spirituality. This study applied a qualitative approach with key informants referring to the student members of the spirituality SAU at IAIN Curup in the academic year of 2019/2020. Data collection was carried out by observation and in-depth interviews, and the analysis was further carried out using the Miles’ et al. approach composed of data reduction, data presentation, and conclusion drawing. This study drew a conclusion that: The process of inculcating Islamic educational values carried out in the spirituality SAU by means of mentoring started from the opening, core activities, closing, and evaluation stages. The values of Islamic education instilled extended to faith, worship, and morals realized from various activities or programs existing in the spirituality SAU, such as Silaturahim, ifthor jama'i, rihlah or tadabbur of nature and visitation of figures.